THE EFFECT OF PARENTS' MOTIVATION ON STUDENT'S LEARNING ACHIEVEMENT DEPARTMENT OF BUILDING SMK NEGERI 3 TONDANO: Motivasi orang tua - Rifa Tingon; Rolly R. Oroh; Djubir R.E. Kembuan (GEARBOX: Jurnal Pendidikan Teknik Mesin, 2022)
ABSTRACT This research is a research with a correlational survey method which aims to determine the effect of parental motivation on student achievement in the construction department of SMK Negeri 3 Tondano which was carried out from August to November 2019. The data collection techniques and tools in this study used research instruments in the form of questionnaires and report cards. Based on these data, it is known that the significance value is 0.000 with a large correlation coefficient of 0.901 with a coefficient of determination of 81.18%, which means that any changes that occur in learning outcomes are influenced by the teacher's personality competence of 81.18% and the rest is influenced by other variables. And to determine the level of influence of parental motivation on student achievement, that is by comparing the values ​​of t count and t table. This correlation test shows the value of t count > t table (19,386 > 1,660). Thus the researcher concludes that the role of parents in improving student achievement in the Department of Building SMK Negeri 3 Tondano is quite large,